CRIMES PERPETRATED AGAINST WOMEN IN A CITY OF NORTH INDIA - Mutneja, Anu; Farooq, Aasiya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the patterns and prevalence of crimes perpetrated against women in Srinagar, a city in Kashmir, Northern India, where socio-political conflicts and gender-based violence are deeply intertwined. It explores various forms of violence, including domestic violence, sexual assault, honour killings, and harassment, amidst the backdrop of Kashmir's complex socio-political landscape. Using data from the Women's Harassment Cell in Srinagar, the study presents a quantitative analysis of 136 cases of violence against women, focusing on the socio-demographic characteristics and types of crimes. The results highlight that domestic violence is the most prevalent crime (50%), followed by drug abuse-related violence (25%). The study also sheds light on the socio-economic challenges faced by women, with a significant number of victims coming from lower socio-economic backgrounds. Key findings suggest a correlation between violence and cultural, legal, and psychological factors exacerbated by the region's prolonged conflict. The research aims to enhance understanding of the systemic inequalities faced by women in Kashmir and calls for comprehensive legal and social reforms to address these pervasive issues.